2016 IEEE Global Conference on Signal and Information Processing (GlobalSIP) 2016
DOI: 10.1109/globalsip.2016.7905945
|View full text |Cite
|
Sign up to set email alerts
|

Energy-efficient joint transmit beamforming and subarray selection with non-linear power amplifier efficiency

Abstract: Another important fact arising from the use of large numbers of antennas is the limited numbers of RF chains, i.e., the latter may be smaller than the former. This means that the beamforming gain and the number of parallel streams becomes limited. However, huge numbers of antenna elements can be installed in the transmitter in particular at higher center frequencies, like mm-waves [11]. The same has also been proposed for more conventional microwave frequencies below 10 GHz [11]. One option to benefit from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…We focus on the nonconvex convexity induced by (19), (22), (25d), and (46b). Again, by using the change of variables in Section III-B1 and introducing additional variables, we transform (46) into the following equivalent problem minimizẽ q,w,r,τ ,η v,s,u,t,zη…”
Section: Solution For Eef-twmentioning
confidence: 99%
See 2 more Smart Citations
“…We focus on the nonconvex convexity induced by (19), (22), (25d), and (46b). Again, by using the change of variables in Section III-B1 and introducing additional variables, we transform (46) into the following equivalent problem minimizẽ q,w,r,τ ,η v,s,u,t,zη…”
Section: Solution For Eef-twmentioning
confidence: 99%
“…However, signal processing power is often rate-dependent [19] and PAs' efficiency depends on output power level [20]. It has been demonstrated that such aspects may have significant impacts on the network level EE performances [21], [22].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…bu }) is some feasible point of (24). As a result, we arrive at the approximate convex program at iteration n as maximize v,η,z,t,{g bu } η subject to {(4), (5), (24c), (24d), (25), (26)}.…”
Section: Lemma 3 Problemsmentioning
confidence: 99%
“…However, in practice, PA efficiency is highly dependent on the output power region and the employed PA type. To account this, the non-linear power consumption models of PAs have been introduced [21][22][23][24] in which the PA efficiency of RF chain m at BS b is expressed as…”
Section: Power Dissipated On Pasmentioning
confidence: 99%